2014
DOI: 10.1016/j.stem.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Potential of iPSCs Is Greatly Influenced by Reprogramming Factor Selection

Abstract: Summary Induced pluripotent stem cells (iPSCs) are commonly generated by transduction of Oct4, Sox2, Klf4, and Myc (OSKM) into cells. Although iPSCs are pluripotent, they frequently exhibit high variation in terms of quality, as measured in mice by chimera contribution and tetraploid complementation. Reliably high-quality iPSCs will be needed for future therapeutic applications. Here, we show that one major determinant of iPSC quality is the combination of reprogramming factors used. Based on tetraploid comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 62 publications
8
135
0
3
Order By: Relevance
“…It has been shown that virus-mediated reprogramming of bovine somatic cells required the addition of ectopic NANOG cDNA to the Oct4, Klf4, Sox2, and c-Myc (OKSM) factors for successful epigenetic reprogramming (Sumer et al, 2011). These data are in accordance with a recent study in the mouse (Buganim et al, 2014) showing that the quality of murine iPSC lines correlated positively with the number of reprogramming factors used. The biPS-1 cell line in the present experiments was established with the aid of the PB-6F transposon, which contains NANOG and LIN28.…”
Section: Discussionsupporting
confidence: 83%
“…It has been shown that virus-mediated reprogramming of bovine somatic cells required the addition of ectopic NANOG cDNA to the Oct4, Klf4, Sox2, and c-Myc (OKSM) factors for successful epigenetic reprogramming (Sumer et al, 2011). These data are in accordance with a recent study in the mouse (Buganim et al, 2014) showing that the quality of murine iPSC lines correlated positively with the number of reprogramming factors used. The biPS-1 cell line in the present experiments was established with the aid of the PB-6F transposon, which contains NANOG and LIN28.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, this observation appears to support recent reports highlighting the importance of Esrrb in establishing pluripotency and self-renewal independent of Sox2. [34][35][36] Buganim et al 34 reported that combination of Esrrb, Nanog, Sall4 and Lin28 can efficiently support pluripotency with a quality higher than other factor combinations, including Oct4, Sox2, Klf4 and Myc. 34 Interestingly, in addition to Esrrb and Nanog, the expression levels of Lin28 and Sall4 also maintain at a higher expression level in U1 and U2 cells (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…By screening diverse factors that are normally expressed in pluripotent stem cells (PSCs), but not fibroblasts, for their ability to convert fibroblasts to pluripotency, the transcription factors Oct3/4, Sox2, Klf4, and c-Myc (O, S, K, and M) were found to trigger endogenous expression of pluripotent factors and be sufficient to reprogram fibroblasts into induced PSCs (iPSCs) (Takahashi and Yamanaka 2006). Although alternative sets of transcription factors for iPSC reprogramming have been reported (e.g., Buganim et al 2014), most studies include Oct3/4 and/or Sox2 (Yu et al 2007;Feng et al 2009;Han et al 2010;Gao et al 2013). How does this set of factors first interact with their target sites to initiate reprogramming?…”
Section: Pioneer Factors In Cell Reprogrammingmentioning
confidence: 99%